The Impact of Trade and Investment Policies on the Labour Standards in the Mauritian and Namibian Export Processing Zones: Lessons for Rwanda - Nankunda, Jackie (Department of Commercial Law, 2014)
Export Processing Zones (EPZs) have become rather popular trade and investment policy instruments used by governments to promote trade and Foreign Direct Investment (FDI). The trend of establishing EPZs was started by the creation of the Shannon Free Zone in late 1950s in Ireland, a zone that now boosts over 100 international manufacturing companies. It was the success of this first zone that encouraged many countries to create their own EPZs in the hope that the incentives would encourage industrial development. The World Bank regards the increasing introduction of EPZs as a signal of a country's departure from import substitution towards an export-oriented economy.